Human Resources in Public Administration – Current Challenges and Expectations (The Polish-Lower Silesian Perspective) - Korczak, Jerzy (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
The paper touches on issues of contemporary public administration in the context of the condition of its human resources, taking as a starting thesis the dependence of the effectiveness of the administration on the effectiveness of its personnel which is a function of the level and quality of qualifications. The article points out that legislation setting forth employment guidelines for civil service positions affects the quality of the personnel. The regulations affect personnel selection, development of its professional career paths and, through appropriate assessment, not only a reasonable promotion but also a necessary selection. The instability of the regulations and their poor quality adversely affect the condition of the personnel, which is mirrored in the low-quality effectiveness of actions taken by the personnel as well as in the sagging interest of younger generations in public administration jobs, which threatens a disruption in the natural generation exchange.
Keywords: współczesna administracja publiczna; zasoby ludzkie; efektywność administracji; efektywność kadr administracyjnych